2013
DOI: 10.1017/s0022029913000526
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion properties of potentially probioticLactobacillus kefirito gastrointestinal mucus

Abstract: We investigated the mucus-binding properties of aggregating and non-aggregating potentially probiotic strains of kefir-isolated Lactobacillus kefiri, using different substrates. All the strains were able to adhere to commercial gastric mucin (MUCIN) and extracted mucus from small intestine (SIM) and colon (CM). The extraction of surface proteins from bacteria using LiCl or NaOH significantly reduced the adhesion of three selected strains (CIDCA 8348, CIDCA 83115 and JCM 5818); although a significant proportion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 45 publications
3
32
0
1
Order By: Relevance
“…In turn, Sánchez et al (2009) reported preliminary results regarding the interaction of B. cereus' SLPs with commercial porcine gastric mucins. Recently, Carasi et al (2014) reported that L. kefiri strains treated with NaOH and LiCl have a lower capacity to adhere to porcine gastric mucin and mucus components extracted from piglet small intestine and colon. Moreover, the addition of soluble SLPs increased L. kefiri adhesion to these substrates, suggesting that the presence of these proteins in the gastrointestinal tract could enhance the bacterial adhesion to mucus layer, improving the interaction with the epithelium (Carasi et al 2014).…”
Section: Adhesion To Epithelial Cells Gastrointestinal Mucus and Extmentioning
confidence: 99%
See 1 more Smart Citation
“…In turn, Sánchez et al (2009) reported preliminary results regarding the interaction of B. cereus' SLPs with commercial porcine gastric mucins. Recently, Carasi et al (2014) reported that L. kefiri strains treated with NaOH and LiCl have a lower capacity to adhere to porcine gastric mucin and mucus components extracted from piglet small intestine and colon. Moreover, the addition of soluble SLPs increased L. kefiri adhesion to these substrates, suggesting that the presence of these proteins in the gastrointestinal tract could enhance the bacterial adhesion to mucus layer, improving the interaction with the epithelium (Carasi et al 2014).…”
Section: Adhesion To Epithelial Cells Gastrointestinal Mucus and Extmentioning
confidence: 99%
“…Recently, Carasi et al (2014) reported that L. kefiri strains treated with NaOH and LiCl have a lower capacity to adhere to porcine gastric mucin and mucus components extracted from piglet small intestine and colon. Moreover, the addition of soluble SLPs increased L. kefiri adhesion to these substrates, suggesting that the presence of these proteins in the gastrointestinal tract could enhance the bacterial adhesion to mucus layer, improving the interaction with the epithelium (Carasi et al 2014). Since differences in the adhesion ability of L. kefiri strains to mucus and enterocytes were observed after in vitro simulation of gastrointestinal tract conditions (pH, biliar salts and enzymes) we are currently investigating the role of SLP in this phenomenon.…”
Section: Adhesion To Epithelial Cells Gastrointestinal Mucus and Extmentioning
confidence: 99%
“…In previous studies, our workgroup has demonstrated that secretion products and surface proteins from L. kefiri exert a protective action against the invasion of Salmonella enterica serovar Enteritidis to Caco-2 cells [27] and also against the cytotoxic effects of clostridial toxins on Vero cells [28]. Moreover, L. kefiri strains have been proven to be safe [29] and to adhere to gastrointestinal mucus [30]. On the other hand, L. kefiri strains preserve a high percentage of viability after both spray-drying [31, 32] and freeze-drying procedures [33].…”
Section: Introductionmentioning
confidence: 99%
“…The Shiikuwasha pomace fermented by L. plantarum E58 might be useful for feeding pigs, because strain E58 showed good survival and adhesion to porcine gastric mucin at low pH. Some strains of Lactobacillus kefiri can adhere to mucin derived from the small intestine and colon as well as gastric mucin (Carasi et al ., ). The ability of the strains tested herein to adhere to gastric mucin may contribute to maintaining gastrointestinal health.…”
Section: Resultsmentioning
confidence: 97%